Penggunaan Probiotik Dan Magot Untuk Mereduksi Lalat di Peternakan Ayam Pedaging Muara Selayar Desa Pijot - Muhamad Ali; Made Sriasih; Anwar Rosyidi; I Wayan Wariata; Muh. Aidil Fitriyan Fadjar Suryadi; Nefi Andriana Fajri; Sulaiman Ngongu Depamede (Jurnal Gema Ngabdi, 2022)
Chicken manure waste is one of the main problems for large-scale broiler cultivation, especially in areas close to residential areas. The accumulation of manure that accumulates under the cage attracts the arrival and development of the flies in the cultivation site. The development of these flies will spread to the houses of residents who live around the cage. As a result, many farmers stop cultivating the broilers because of public complaints. To overcome this problem, the use of probiotics from acetic acid-producing bacteria can be used to reduce the development of flies because of the ability of the bacteria to reduce the pH of the media and create an uncomfortable environment for egg growth. Likewise, the development of maggot can be a competing medium that beats the flay. In community service activities regarding "The use of probiotics and maggot production to reduce flies in the Muara Selayar broiler farm, Pijot Village, Keruak District, East Lombok Regency". Through this activity, the development of flies can be emphasized by the use of probiotics and the development of magot which can be used as chicken feed.